Impact of percent positive random biopsies on biochemical outcome in prostate cancer patients treated with external beam radiotherapy with or without androgen deprivation - (:unkn) unknown (ZERBINIS MEDICAL PUBL, 2009)
Purpose: To identify the prognostic factors for biochemical outcome in patients with localized prostatic adenocarcinoma treated with external beam radiotherapy (EBRT) with or without androgen deprivation (AD) and to investigate the impact of percent positive prostate core biopsies (PCB%). Methods: From 1998 through 2003, 333 patients with newly diagnosed localized prostate cancer were retrospectively analyzed. The patients were treated in two institutions with definitive EBRT to a median dose of 72 Gy and 80% of them received short- or long-term AD. Biochemical failure, was defined using ASTRO criteria with 3 consecutive rises in prostate specific antigen (PSA). Results: Median follow up was 36 months. Gleason score, initial PSA, risk grouping, PCB%, AD and total duration of AD were found to be significant predictors for biochemical outcome in univariate analysis. Independent predictors for PSA failure, on multivariate analysis were PCB% and duration of AD. Among 3 risk groups, in the intermediate risk group the biochemical control was significantly better in patients with < 67% positive core biopsies. In the subgroup analysis of patients who received a prostatic dose <= 70.2 Gy and patients with no hormonal or short-term hormonal manipulation the 5-year biochemical outcome was significantly reduced in patients with >= 67% positive core biopsies. These significant differences did not exist in patients receiving > 70.2 Gy and long-term hormonal therapy. Conclusion: Our results suggest that high PCB% could be a predictor of biochemical relapse, especially in the intermediate risk group. The role of PCB% in prostate cancer should be investigated in further trials.
Keywords: core biopsies; external beam radiotherapy; percent positive cores; prostate cancer; RADIATION-THERAPY; RADICAL PROSTATECTOMY; CLINICAL UTILITY; ADENOCARCINOMA; DISEASE; ANTIGEN; CORES; GY